Fashion fads through American history : fitting clothes into context - Moore, Jennifer Grayer (Santa Barbara, California : Greenwood, an imprint of ABC-CLIO, LLC, 2016)
"The primary purpose of this book is to document fashions that are typically overlooked by sources that survey the broad historical record of dress practices. Surveys of historical fashion purposely and rightfully document and explain the long-lasting fashion trends that may be said to define the visual landscape of dress in a given period. Fads, in contrast to trends, are shorter-lived, potentially not as widespread across demographics of age and income, and may be viewed as oddities or outliers once their period of popularity has passed. Therefore, this book fills a gap in the existing literature by documenting and highlighting important but overlooked fashion phenomena. Though most fads had short spans of popularity (or relatively short spans given their time period), fashion fads are culturally significant. Although fashion fads may be outrageous in appearance, may be difficult or unwieldy to wear, may break rules of decorum, or may otherwise seem to be out of step with the culture at large, fashion fads are emblematic of attitudes and ideas that existed in an historical period. Fads have the special ability to reveal feelings, dispositions, and values that might not be well understood through other historical source material. Therefore a book dealing with fashion fads is an excellent tool for the student or scholar who seeks to develop an integrated point of view about the historical past"--
1. From a Land Far Away : Foreign and Exotic Elements Infiltrate American Fashion -- 2. Looking Glass Lunacy : Wild and Wonderful Hair and Makeup Fads -- 3. Wild New Proportions : The Long and Short and Wide and Slender Shapes of Faddish Apparel -- 4. Living out the Fantasy : Television, Music, and Movies Take to the Streets -- 5. High Tech Fashions : Fads on the Cutting Edge -- 6. Self-Styled, Reworked, and Re-imagined : Consumers in Control of Fashion Fads -- 7. Old Apparel, New Context : The Fads and Potential Faux Pas of Dressing Outside of Conventions -- 8. Radical Materials : These Are Such Stuff As Fads are Made On -- 9. Beyond Compare : Iconic and Outrageous Fashion Fads.
Includes bibliographical references and index.
Print version record.
Keywords: Fashion -- United States -- History; Clothing and dress -- United States -- History; Fads -- United States -- History; United States -- Social life and customs; Popular culture -- United States -- History; SOCIAL SCIENCE / Popular Culture; HISTORY / United States / General; Clothing and dress; Fads; Fashion; Manners and customs; Popular culture; United States; HEALTH & FITNESS / Beauty & Grooming; History; Electronic books